Juvenile Idiopathic Arthritis in a Tertiary Rheumatology Clinic - Oguntona Segun Akintayo; Olatunde Olabanke Arike; Fawole Ayodeji Emmanuel (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2018)
Background: Juvenile Idiopathic Arthritis (JIA) is one of the common chronic diseases in childhood. The inflammatory process in the joint is triggered by pro-inflammatory cytokines. The treatment is directed at alleviation of pain, inhibition of disease activity and preservation of range of motion. Objectives: To describe the spectrum of clinical presentations, laboratory parameters and drug therapy among patients with Juvenile Idiopathic Arthritis seen at a Tertiary Health Centre. Methods: All the patients who fulfilled the classification criteria of the International League of Associations for Rheumatology for JIA between July 2012 and June 2016 were included in the study. The clinical features, results of laboratory investigations and the treatment received were recorded. Results: A total of 1910 patients were seen at the Out-Patient Rheumatology Clinic over the 4-year period but only 18 case files of patients with JIA (0.95% of total) were retrieved. There were 13 females and 5 males with a female-to-male ratio of 2.6:1. The age range was 8-15 years with a mean of 10.3 ± 2.1 years. The duration of symptoms prior to presentation ranged between 2 years and 7 years with a mean of 4.2 ± 1.3 years. Polyarticular presentation was observed among 61.1% (11/18), pauciarticular in 27.8% (5/18) and systemic in 11.1% (2/18). Fever was uniformly seen among the patients with systemic onset, while fever and joint swelling were the common presentations in the other groups. Knee and ankle joints were most commonly affected. Erythrocyte Sedimentation Rate was elevated in 88.9% of the patients. Methotrexate was used in 61.1% and combination therapy was used as necessary. Conclusion: JIA is relatively uncommon in the setting of study. Polyarthritis form of JIA was the commonest type and response to steroid was uniformly good. Early recognition of the subtypes of JIA will enhance effective management of cases.